QUALITY OF HUMAN RESOURCE SERVICES IN OUTPATIENT CARE ON OUTPATIENT SATISFACTION IN HOSPITALS (SYSTEMATIC LITERATURE REVIEW) - Lia Mirawati; M. Rizal Fauzi; Yani Restiani Widjaja (Antis Publisher, 2024)
This study aims to assess the relationship between the quality of outpatient human resource (HR) services and outpatient satisfaction in hospitals through a systematic literature review method. The quality of health HR services is an important factor that affects patient satisfaction, which can ultimately affect loyalty and recommendations from patients. In this review, we analysed various studies published in a given period that evaluated the quality of HR services in outpatient care and their impact on patient satisfaction. Using systematic literature review (SLR) research on research published in high-reputation journals, using PRISMA diagrams for the research method. The results of the literature review show that aspects such as speed of service, competence of medical staff, availability of facilities, and effective communication between service providers and patients are the main factors contributing to patient satisfaction. In addition, the study found that improvements in the quality of outpatient HR services were significantly correlated with higher levels of patient satisfaction. This study concludes that hospitals need to focus on improving the quality of outpatient HR services through staff training, facility improvement, and service management system improvement to achieve optimal patient satisfaction. These findings provide insights for hospital managers and policymakers in formulating strategies to improve service quality and patient satisfaction.